Al-Buqa’i’s Approach In His Book Masa’id Al-Nazr For Supervising The Objectives Of The Surahs (Journal of the College of Basic Education, 2025)
The research aims to explain the approach of Imam Al-Baqaei in his book "Masa'id Al-Nazar li-Ashraf ala Maqasid Al-Sur" This book Which is considered one of the most prominent works in this field specialized in explaining the objectives of the Quranic surahs, was a great addition to the Islamic library, as it added something new, which is the science of occasions and the science of the objectives of the surahs, and although he was not the first to write about them, he was the first to devote them to independent books. Research plan: The research consisted of An introduction and two sections, the first section includes dealt with: A general view of Al-Baqaei's approach in his book (Masa'id Al-Nazar li-Ashraf ala Maqasid Al-Sur) and included six demands. As for the second chapter: Clarification of the thematic unity and applications on Surat Al-Baqarah. Conclusion: It included the results reached by the research, and a list of the names of sources and references.